Assessment of Enterprise Resource Planning systems in the Central Bank of the Republic of Azerbaijan: In the case of Financial Market Regulation and Supervision - Garayev, Siraj (ADA University, 2021)
Ensuring effective and efficient financial market supervision is challenging when a financial supervisory authority covers diverse range of financial institutions with unique risk profiles. Those authorities are therefore seeking Enterprise Resource Planning (ERP) systems in order to leverage technology based solutions to enhance the efficiency and effectiveness of their regulatory and supervisory roles. In Azerbaijan the Central Bank of the Republic of Azerbaijan (CBAR) is assigned as the mega regulator in financial sector from 2020 on. Given that CBAR’s supervision involves a large number and a various types of financial institutions, it must deal with complex supervisory tasks to ensure compliance with regulatory requirements. The objective of this study is to assess the ERP systems in CBAR used in financial market supervision. The research was conducted in a qualitative fashion by interviewing CBAR’s professionals to determine efficiencies and deficiencies of the existing ERP systems of CBAR by measuring how effective is the supervisory capacity in CBAR. The findings showed that CBAR has several useful supervisory systems in place. However, it is lacking numerous necessary supervisory solutions to attain its supervisory goals. Without relevant ERP systems, CBAR is unable to effectively apply risk-based supervision, focus on risk profile of financial institutions and prioritize supervisory actions with targeted allocation of resources. To address the deficiencies identified, the study also provided recommendations to develop an integrated ERP systems for financial market supervision. This thesis adds to the work on supervisory technology in financial market supervision. It may also be particularly useful to CBAR to develop adequate systems within the organization.
Keywords: Business; Business; SupTech.; Data collection.; Data analytics.; Financial markets.